Effects of Automated Emergency Braking and Seatbelt Pre-Pretensioning on Occupant Injury Risks in High-Severity Frontal Crashes - Mishra, Ekant; Mroz, Krystoffer; Pipkorn, Bengt; Lubbe, Nils (Frontiers in Future Transportation, 2022)
In high-severity crashes, occupant protection is challenging. Automated Emergency Braking (AEB) and seatbelt pre-pretensioning (PPT) are means to improve occupant protection; the purpose of this study was to quantify their effects on occupant injury risks in high-severity full-frontal crashes by Finite Element (FE) simulations. The SAFER Active average male Human Body Model was used as an occupant substitute. The crash pulses used were from separate full-frontal crash simulations using a Honda Accord FE model. The vehicle interior model comprised a seat, an instrument panel, a three-point pretensioned seatbelt system with a load-limiter of 3.1 kN force level, and a frontal passenger airbag. The effects of AEB and PPT were evaluated by simulating a 1 g pre-crash braking scenario for 0.5 s, with and without AEB, for three different PPT force levels: 0 N, 300 N, and 600 N. The impact speed of 80 km/h was reduced to 69 km/h by AEB. When neither system was activated, the predicted risk for an occupant to sustain two or more fractured ribs (NFR2+) was 100% for both 45- and 65-year-old male occupants. The risks were reduced when the AEB was activated, particularly for the 45-year-old occupant. When the AEB was activated, the risks of concussion and rib fractures were reduced; upper neck tension forces, pelvis Anterior Superior Iliac Spine (ASIS) forces, and lower extremity forces were also reduced. Increasing the PPT forces reduced the rib fracture risk further (to about 48% for a 45-year-old occupant with 600 N PPT force). The reduced speed due to AEB resulted in a lower concussion risk (from 71.3% to 31%). However, the concussion risk increased slightly with increased PPT forces.